2018
DOI: 10.1103/physrevd.97.065004
|View full text |Cite
|
Sign up to set email alerts
|

Decaying massive particles in the matter and radiation dominated eras

Abstract: According to the standard model of cosmology, the early universe has been dominated by radiation or non-relativistic matter in several eras of its history. However, many cosmological calculations involving particle processes are commonly done using Minkowskian results for them, although, for more precise treatment, quantum field theory in curved spacetime is needed. This paper aims to fill this gap by presenting decay rates for matter and radiation dominated universes in this more precise treatment. We provide… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 19 publications
0
34
0
Order By: Relevance
“…It was found that Minkowskian and curved space decay rates produce results within the same order of magnitude with only small numerical differences. Although it is known that decay rates in curved space are modified from their Minkowskian counterparts [20,21,24], it is likely that the timescales in question are so small that the effect of curved space modification has not produced noticeable effects yet.…”
Section: Discussion and Outlookmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that Minkowskian and curved space decay rates produce results within the same order of magnitude with only small numerical differences. Although it is known that decay rates in curved space are modified from their Minkowskian counterparts [20,21,24], it is likely that the timescales in question are so small that the effect of curved space modification has not produced noticeable effects yet.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…When curvature cannot be neglected anymore, Minkowskian decay rates are nevertheless only an approximation and curved space counterparts should be used instead. This problem has attained a wealth of interest in recent times and decay rates have been obtained for various processes [20][21][22]. For more on the conceptual and technical issues regarding particle decay in curved spacetime, we refer the reader articles [20-22, 25-27, 32, 33].…”
Section: Decay In Curved Spacetimementioning
confidence: 99%
“…At the same time, the simplified versions of the model (1) are known as useful tools in cosmology. E.g., in the well-known papers [33,34] (see further references therein, also the recent work [35]) the scalar field χ describes the Bose-Einstein condensate of some more fundamental fields. The considerations in these works involves not only tree-level, but also the loop effects.…”
Section: Discussionmentioning
confidence: 99%
“…The only difference compared to the case of a real index is the different exponential factor with the consequence that it is not cancelled by the square of the absolute value in Eq. (14). Performing a change of variables to u = 2bmη (2+n)/2 /(2 + n), we are left with…”
Section: B Imaginary Indexmentioning
confidence: 99%
“…In the present paper we focus on a more thorough treatment of particle decay in spatially flat Friedmann-Robertson-Walker (FRW) universes with a general power-law expansion and a priori unrestricted gravitational coupling, extending previous analyses of Refs. [14,15]. This was done using the method of added-up probabilities originally introduced in Ref.…”
Section: Introductionmentioning
confidence: 99%